Integration Between Adat and Islam in the Practice of Religious Freedom in West Sumatra - Ashadi, Andri; Sefriyono, Sefriyono; Zulfis, Zulfis; Tanggok, Muhammad Ikhsan (Journal of Al-Tamaddun, 2025)
This article explores the concept of local wisdom of the Bodi Caniago adat [custom] and the Tarekat Shattariyyah as the basis for religious freedom in the Sungai Buluh Minang Community (SBMC) of Padang Pariaman, West Sumatra. The article was not merely based on a literature review, but was also supported with observations and interviews with traditional and tarekat leaders between 2017-2018 to show an accommodative relationship between religious freedom in the Nias Community (NC) and Islamic humanism as the SBMC’s local wisdom. The findings show that the existence of houses of worship for minority groups and the freedom to practice religion in them is made possible through the legitimate support of traditional and popular religious institutions (tarekat) which are inclusive because they emphasize equality and humanity (tolerance). Equality reflected in the concept of deliberation and consensus in the Bodi Caniago custom has provided space for religious freedom for the Nias Community (NC). At the same time, tolerance which emphasizes respect for humans and different entities including NC in the Tarekat Shattariyyah further strengthens it. Theoretically, the values of equality and tolerance reflect the discourse of Islamic humanism which is marked by an anthropo-cosmic human that connects God, nature and humans, as well as a pluralistic epistemology between tradition, Islam and a sense of responsibility towards society. This article argues that values such as equality and tolerance which are deeply-rooted in Islamic humanism are compatible with human rights, especially religious freedom, as a civilized practice based on religion.